2020
DOI: 10.1007/s13402-020-00553-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The POU2F1/miR-4490/USP22 axis regulates cell proliferation and metastasis in gastric cancer

Abstract: Purpose Growing evidence indicates that aberrant expression of microRNAs contributes to tumor development. However, the biological role of microRNA-4490 (miR-4490) in gastric cancer (GC) remains to be clarified. Methods To explore the function of miR-4490 in GC, we performed colony formation, EdU incorporation, qRT-PCR, Western blotting, in situ hybridization (ISH), immunohistochemistry (IHC), flow cytometry, ChIP and dual-luciferase reporter assays. In addition, the growth, migration and invasion capacities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Previous studies have demonstrated that POU2F1 plays a crucial role in promoting the progression of several tumors [ 10 , 18 , 29 , 30 ]. To determine the expression of POU2F1 and TTC3-AS1 in GC, 10 paired gastric tumor tissues and adjacent normal tissues were detected using qRT-PCR and western blot.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated that POU2F1 plays a crucial role in promoting the progression of several tumors [ 10 , 18 , 29 , 30 ]. To determine the expression of POU2F1 and TTC3-AS1 in GC, 10 paired gastric tumor tissues and adjacent normal tissues were detected using qRT-PCR and western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of public databases indicated that POU2F1 exhibited higher expression in renal, ovarian, and esophageal cancers while lower expression in the cerebral tumor, bladder cancer, and liposarcoma, compared with NCs. Recent studies have indicated that POU2F1 was highly expressed in GC patients [ 34 36 ]. In this study, we also identified that POU2F1 and its potential target TTC3-AS1 were significantly upregulated in GC tumor tissues, compared with normal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MicroRNAs (miRNAs) are endogenous 19-23 nucleotide (nt) RNAs and pair with mRNAs of protein-coding genes to suppress translation and degrade mRNAs in post-transcriptional level (11). miRNAs are related to cellular proliferation, differentiation, apoptosis, migration, invasion and inflammation (1216). Additionally, miRNAs play a crucial regulatory role in host immune response to pathogenic infection.…”
Section: Introductionmentioning
confidence: 99%